Clinical and Genetic Spectra of Inherited Liver Disease in Children in China - Fang, Youhong; Yu, Jindan; Lou, Jingan; Peng, Kerong; Zhao, Hong; Chen, Jie (Frontiers in Pediatrics, 2021)
Background: Children presenting with chronic liver disease or acute liver failure often have an underlying genetic disorder. The aim of this study was to analyze the clinical and genetic spectrum of children with inherited liver disease in a tertiary hospital. Methods: A total of 172 patients were classified into three groups according to their clinical presentation: cholestasis (Group A), liver dysfunction (Group B), and hepatosplenomegaly with or without liver dysfunction (Group C). Next-generation sequencing (NGS) was performed on all patients recruited in this study. The genotypic and phenotypic spectra of these patients were reviewed. Results: The median age at admission of the 172 patients is 12.0 months (IQR: 4.9, 42.5), with 52.3% males and 47.7% females. The overall diagnostic rate was 55.8% (96/172) in this group. The diagnostic rates of whole-exome sequencing (WES) and targeted gene panel sequencing (TGPS) were 47.2% and 62.0%, respectively (no significant differences, p=0.054). We identified 25 genes related to different phenotypes, including 46 novel disease-related pathogenic mutations. The diagnostic rates in three groups were 46% (29/63), 48.6% (34/70) and 84.6% (33/39), respectively. ATP7B, SLC25A13 and G6PC are the top three genes related to monogenic liver disease in this study. Conclusion: WES and TGPS show similar diagnostic rates in the diagnosis of monogenic liver disease. NGS has an important role in the diagnosis of monogenetic liver disease, which can provide more precise medical treatment and predict the prognosis of these diseases.